Do Determinants of Firm Value Influence Profitability? Exploring the Moderating Role of Financial Technology - Munawar, Andri Helmi; Hidayat, Deny; Rosyadi, Agi (JMB : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the factors that affect firm value by considering the role of profitability as a mediating variable and financial technology (fintech) as a moderating variable. The independent variables studied include liquidity and leverage. The research method used is a quantitative approach with moderated mediation regression analysis. The sample consists of 21 banking companies listed on the Exchange Indonesia (IDX) in the Stock period 2018-2023, with purposive sampling . techniqueThe results showed that liquidity has a has significant effect on firm value, while leverage no direct effect. Profitability is proven to act as a mediator in the relationship between between liquidity and firm value (complementary ) mediationmediator and as a full (full mediation). in the relationship leverage and firm value In addition, fintech acts as a moderator in the relationship between liquidity and profitability, as well as leverage and profitability. This suggests that the adoption of fintech can strengthen the impact of liquidity and leverage on profitability, which in turn contributes to increasing firm value. The implications of this study highlight the importance of optimal and leverage , liquidity managementas well as the utilization of fintech in in the improving profitability and firm value banking sector. Keywords: Liquidity, Leverage, Profitability, Fintech, Firm Value,